Nutraceutical Potential and Processing Aspects of Oyster Mushrooms (Pleurotus Species) - Kumar, Krishan (Current Nutrition & Food Science, 2020)
Background: Oyster mushrooms (Pleurotus species) have gained considerable attention of food technologist and nutritionist for their nutraceutical properties. Oyster mushrooms are considered as functional foods due to their richness in functional food ingredients. In recent times, consumption of these mushrooms has increased considerably due to their numerous health benefits. These are potential sources of bioactive components, which are sufficient enough for prevention and treatment of various lifestyle diseases. There are about 200 different species in the genus Pleurotus and these are commonly referred to as “oyster mushrooms”. Objective: The study aimed to grasp a collective information on nutraceutical and processing aspects of highly perishable but nutritious oyster mushroom Results: Pleurotus ostreatus is the most commonly consumed species all over the world due to its superior flavor, taste and nutraceutical properties. It acts as a source of natural antioxidants which might be beneficial for human health in preventing or reducing oxidative damage. Nutritionally, these species are rich sources of proteins, dietary fibres, β-glucan, vitamin B-complex, vitamin C and minerals. They contain higher proportions of certain amino acids such as methionine, cystine and aspartic acid than other edible mushrooms. Oyster mushrooms have been reported to possess hypocholesterolemic, anti-bacterial, anti-diabetic, anti-oxidant, anti-arthritic, anti-carcinogenic, hepatoprotective, anti-viral activities and act as natural resources of immunotherapy activities. The use of these mushrooms can overcome the deficiency of protein in the developing countries where there is unavailability or unacceptability of good quality proteins from animal sources because of religious restrictions. Conclusion: Because of the occurrence of abundant nutritional ingredients and other bioactive components in P. ostreatus, they have a great scope as a potential source for the development of functional or specialty foods for value addition of deficient foods so as to alleviate the nutritional deficiency diseases from society.
Keywords: nutritional